Caracterização de subpopulações de interneurônios imunorreativos para proteínas ligantes de cálcio no córtex pré-frontal do Sagui (Callithrix jacchus): distribuição e morfologia - Silva, Joanilson Guimarães (2011)
Cortical interneurons are characterized by their distinct morphological, physiological and biochemical properties, acting as modulators of the excitatory activity by pyramidal neurons, for example. Various studies have revealed differences in both distribution and density of this cell group throughout distinct cortical areas in several species. A particular class of interneuron closely related to cortical modulation is revealed by the immunohistochemistry for calcium binding proteins calbindin (CB), calretinina (CR) and parvalbumin (PV). Despite the growing amount of studies focusing on calcium binding proteins, the prefrontal cortex of primates remains relatively little explored, particularly in what concerns a better understanding of the organization of the inhibitory circuitry across its subdivisions. In the present study we characterized the morphology and distribution of neurons rich in calcium-binding proteins in the medial, orbital and dorsolateral areas of the prefrontal cortex of the marmoset (Callithrix jacchus). Using both morphometric and stereological techniques, we found that CR-reactive neurons (mainly double bouquet and bipolar cells) have a more complex dendritic arborization than CB-reactive (bitufted and basket cells) and PV-reactive neurons (chandelier cells). The neuronal densities of CR- and CB-reactive cells are higher in the supragranular layers (II/III) whilst PV-reactive neurons, conversely, are more concentrated in the infragranular layers (V/VI). CR-reactive neurons were the predominant group in the three regions evaluated, being most prevalent in dorsomedial region. Our findings point out to fundamental differences in the inhibitory circuitry of the different areas of the prefrontal cortex in marmoset